2016
DOI: 10.17221/260/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for SMEs in the area of primary agricultural production

Abstract: Th e goal of the paper was to defi ne recommendations of a suitable business strategy for SMEs in the area of primary agricultural production. First, the external environment was analysed to defi ne suitable recommendations for the industry, and also to discover opportunities and threats through fi tting strategic analyses, that aff ect the aforementioned businesses. Secondly, it was necessary to get familiar with the internal environment and functioning of specifi c businesses in the industry (namely those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus, the limiting factor is related to the structure of the employees (insufficient educational structure and professional level), the financial difficulty and the return on investment projects. The solution may be found in different approaches to employees, as a number of authors have suggested in terms of talent management (Egerová et al 2015), and in a well-defined strategy (Chladkova and Formankova 2016;Rolinek anď Rehoř 2008). In spite of the above limits, the Industry 4.0 concept offers great potential for the future, particularly for medium-sized enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the limiting factor is related to the structure of the employees (insufficient educational structure and professional level), the financial difficulty and the return on investment projects. The solution may be found in different approaches to employees, as a number of authors have suggested in terms of talent management (Egerová et al 2015), and in a well-defined strategy (Chladkova and Formankova 2016;Rolinek anď Rehoř 2008). In spite of the above limits, the Industry 4.0 concept offers great potential for the future, particularly for medium-sized enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…Meski berasal dari lingkungan korporasi yang kompleks, analisis SWOT dapat diterapkan untuk menentukan strategi bagi bisnis skala kecil hingga menengah. Penelitian yang dilakukan oleh Chladkova H & Formankova (2016) juga menerapkan analisis SWOT untuk menentukan strategi rantai pasok pada perusahaan kecil dan menengah pertanian. Penelitian lain menggunakan analisis SWOT untuk mengidentifikasi karakteristik yang dapat mendukung rencana jangka panjang konsumsi pangan lokal di Hungaria (Nemeth et al, 2019).…”
Section: Pendahuluanunclassified
“…The problems and prospects of using strategic planning in the activities of agricultural enterprises are studied by scientists from different countries, in particular: J. Jaworski, K. Sokołowska, T. Kondraszuk [5], J. Dyczkowska, T. Dyczkowski [6] (Poland), H. Chladkova, S. Formankova [7] (the Czech Republic), J. Schindler, F. Graef, H. König [8] (Germany), C.-C. Chen, H.-P. Yueh, C. Liang [9] (China), S. Suriyankietkaew, P. Petison [10] (Thailand), R. Kalaki, M. Neves [11] (Brazil). Taking into account the peculiarities of the development of agricultural enterprises, scientists offer various ways to solve existing problems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%